Intrinsically good like god, extrinsically good by god - Chee, Yong Qing (Nanyang Technological University, 2023)
There has been a recent worry for theists: if God is the source of all goodness, does this mean created beings (“creatures”) are not valuable in themselves? Such a challenge has garnered responses to prove the intrinsic value of creatures. However, these responses remain largely silent on the possibility that creatures can be extrinsically valuable at the same time.